PENGARUH MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH BERBANTUAN SLIDE SHARE TERHADAP HASIL BELAJAR KOGNITIF IPS DAN KETERAMPILAN SOSIAL - Udin Cahya Ari Prastya; Sudarmiatin Sudarmiatin; Sumarmi Sumarmi (Graduate School of Universitas Negeri Malang, 2016)
This research is conducted due to the problems faced by the fifth graders of Ampelgading 01 Public Elementary School. They find difficulties in understanding social science subject, indicated by students’ learning outcomes. Only 5% students of class pass the Minimum Passing Criteria of 70. Teacher-centered learning decreases the interaction between teachers and students and students with students, which related to the development of social skills such. Therefore, interactive learning model is needed to build good classroom atmosphere and improve students’ interactions. One model of interactive learning is a Make a Match.This research used quantitative and quasi-experiment methods, Quasi-experimental design used is nonequivalent control group design, using independent t-test assisted with SPSS 16 software for data analysis.The research result presents following the treatment in experimental class using cooperative teaching model ‘Make a Match’ using slide share, average grade of posttest obtained from control group is 66,15 while the experimental class gained the average of 75,18; control class obtained social skills scores with the average of 45 and 61 for experimental class. t test result indicates the cognitive learning measured from gain score of pretest and posttest have significant value of 0.000 and social skills shows significant value of 0.000. It is known that 0.000> 0.05, indicates that is related to the effect of cooperative teaching model ‘Make a Match’ using slide share to the social science cognitive and social skill.Pelaksanaan penelitian ini dikarenakan adanya masalah yang dihadapi oleh siswa kelas V di SDN Ampelgading 01. Meraka merasa kesulitas dalam memahami materi mata pelajaran IPS, hal ini dibuktikan dengan nilai hasil belajar siswa yang mendapatkan nilai di atas KKM dengan nilai KKM 70 hanya 5% dari jumlah total keseluruan siswa. Pembelajaran guru yang bersifat aksi menimbulkan tidak adanya interaksi antara guru dengan siswa dan siswa dengan siswa, hal ini memicu siswa dalam pengembangan keterampilan sosial. Oleh karena itu diperlukan pembelajaran yang menggunakan model pembelajaran interaktif. Salah satu model pembelajaran interaktif adalah model pembelajaran kooperataif Make A Match. Penelitian ini menggunakan jenis penelitian kuantitatif dan jenis eksperimen semu, desain eksperimen semu yang digunakan adalah ”non equivalent control group design”, dengan menggunakan uji t-test independent yang dibantu dengan software SPSS 16 dalam menganalisis data. Dari hasil penelitian setelah kelas eksperimen di berikan perlakuan menggunakan model pembelajaran kooperatif make a match berbantuan slide share didapatkan data postes kelas kontrol rata-rata kelas 66,15 sedangkan kelas eksperimen 75,18, untuk keterampilan sosial skor rata rata kelas kontrol 45 dan kelas eksperimen 61. Data hasil uji t menyatakan hasil belajar kognitif yang di ukur dari gain skor pretes dan postes bahwa nilai signifikannya adalah 0.000 dan untuk keterampilan sosial nilai signifikannya 0.000. Sehingga dapat diketahu bahwa 0.000 < 0.05, dengan demikian dapat di ambil keputusan bahwa ada pengaruh model pembelajaran kooperatif make a match berbantuan slide share terhadap hasil kognitif belajar dan keterampilan sosial siswa.